ANALISIS YURIDIS TINDAK PIDANA PENCABULAN TERHADAP ANAK DI BAWAH UMUR (PUTUSAN PIDANA PURWOREJO NOMOR 57/PID.SUS/2022/PN.PWR) - Aji Benny Wicaksono; Muhamad Hasan Sebyar (JOURNAL OF LAW AND NATION, 2023)
This scientific work aims to finddout what the legalppolicy is for perpetrators of criminal acts of molestation against minors, how the law is applied to perpetratorsdof criminaldacts of molestation againstdminors, and what the criminal responsibility for perpetrators of molestation of minors is in the Purworejo Criminal Decision case. Number 57/Pid.Sus/2022/PN.Pwr. The researchdmethodiused in this research is a normativeijuridical research method soait canabe concluded asafollows: 1. Legal policy is divided into two, namely panel legal policy and non-panel legal policy. 2 Theaapplication ofathe law forathe criminal act of molesting minors is regulatedain the CriminalaCode Articlesa289 toa296, to provide sanctions for perpetrators of criminal actsaof molestingiminors, namelyiby providing inaaccordanceaiwith Law no. 23 of 2002aconcerning ChildaProtection, includingathe provision of prison sentences andafines. 3. The person responsible for the defendant in the case of Purworejo Criminal Decision Number 57/Pid.Sus/2022/PN.Pwr, namely the defendant was foundaguilty becauseahe was provenato have committed an act of sexual immorality against a minor The defendant wasasentenced toaimprisonment for 8 (eight) yearsaand aafine of idr. 60,000,000,- (sixty millionarupiah) withathe provisionathat ifanot replacedaby imprisonmentafor 6 (six)amonths